Tuning Surface Chemistry of Polyetheretherketone by Gold Coating and Plasma Treatment - Novotná, Zdeňka; Rimpelová, Silvie; Juřík, Petr; Veselý, Martin; Kolská, Zdeňka; Hubáček, Tomáš; Borovec, Jakub; Švorčík, Václav (Nanoscale research letters, 2017)
Polyetheretherketone (PEEK) has good chemical and biomechanical properties that are excellent for biomedical applications. However, PEEK exhibits hydrophobic and other surface characteristics which cause limited cell adhesion. We have investigated the potential of Ar plasma treatment for the formation of a nanostructured PEEK surface in order to enhance cell adhesion. The specific aim of this study was to reveal the effect of the interface of plasma-treated and gold-coated PEEK matrices on adhesion and spreading of mouse embryonic fibroblasts. The surface characteristics (polarity, surface chemistry, and structure) before and after treatment were evaluated by various experimental techniques (gravimetry, goniometry, X-ray photoelectron spectroscopy (XPS), and electrokinetic analysis). Further, atomic force microscopy (AFM) was employed to examine PEEK surface morphology and roughness. The biological response of cells towards nanostructured PEEK was evaluated in terms of cell adhesion, spreading, and proliferation. Detailed cell morphology was evaluated by scanning electron microscopy (SEM). Compared to plasma treatment, gold coating improved PEEK wettability. The XPS method showed a decrease in the carbon concentration with increasing time of plasma treatment. Cell adhesion determined on the interface between plasma-treated and gold-coated PEEK matrices was directly proportional to the thickness of a gold layer on a sample. Our results suggest that plasma treatment in a combination with gold coating could be used in biomedical applications requiring enhanced cell adhesion.
Keywords: Cell proliferation; Atomic force microscopy; Plasma treatment; Polyetheretherketone; Mouse embryonic fibroblasts; Gold sputtering; Scanning electron microscopy